Comparison of the Effectiveness of Date Fruit Consumption and Oxytocin Massage on Uterine Involution in Postpartum - Shinta Ika Sandhi; Desi Wijayanti Eko Dewi; Shinta Ayu Nani (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2026)
Postpartum hemorrhage remains a major global health problem and a leading cause of maternal mortality. Effective uterine involution, supported by uterine contractions and the hormone oxytocin, plays a crucial role in preventing hemorrhage. In addition to pharmacological methods, oxytocin stimulation can be achieved non-pharmacologically through oxytocin massage and nutritional support, such as the consumption of date fruit. These two interventions operate through distinct yet complementary mechanisms: neuroendocrine stimulation and metabolic nutritional support. This study aimed to compare the effectiveness of date fruit consumption and oxytocin massage on uterine involution among postpartum mothers. A quasi-experimental pre-test–post-test design was used, with 30 postpartum mothers purposively selected and divided into two groups. The first group consumed 100 g of dates daily, while the second group received oxytocin massage once a day, both for seven days. The results showed that the average reduction in uterine fundal height was 10.47 cm in the date consumption group and 8.07 cm in the oxytocin massage group. An independent t-test confirmed that date consumption was more effective than oxytocin massage at accelerating the reduction in uterine fundal height (p=0.01). Although these findings are limited by the small sample size and purposive sampling method, clinically, both interventions show potential as feasible, low-cost, and culturally acceptable supportive strategies in postpartum care, particularly in resource-limited settings. Further studies with larger samples and more rigorous designs are needed to confirm these results.